DOI-CODI II EXÉRCITO: A EXPERIÊNCIA DE PRESERVAÇÃO DE UM PATRIMÔNIO SENSÍVEL - LEAL NEVES, DEBORAH REGINA (Universidad Nacional del Litoral, 2018)
The DOI-CODI, in São Paulo (Brazil) was a repressive organ that operated between 1969 and 1983 and had as main objective the persecution of opponents of the Civil-Military Dictatorship (1964-1985). In 2010, a group of human rights defense entities requested the preservation of buildings as cultural heritage of the state of São Paulo. The article aims to discuss the process that led to the preservation of the set of buildings, addressing the research methods, the theoretical discussions and the conflicts present in this emblematic case.